Aspects of milk composition and lactation in polar bears - AE Derocher; D Andriashek; John Arnould (1993)
For Ursus maritimus on land, gross energy declined from 16.9 kJ/g for females with 3-month-old cubs to 9.7 kJ/g when offspring were 34 months old. The proportion of females with cubs and yearlings that were lactating declined through the autumn. When female polar bears do not have access to food, those with older offspring cease lactating earlier in the autumn and cessation of lactation results in lower milk fat and energy contents. Changes in milk composition may act to conserve maternal energy stores to ensure survival.